PENGEMBANGAN FORMULASI AROMATERAPI PRODUK HERBAL YANG MENGANDUNG MINYAK ATSIRI BAWANG MERAH (Allium cepa var. aggregatum L ) - Heru Nurcahyo; Aldi Budi Riyanta (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
The using of alternative and complementary therapies as a treatment is growing rapidly, one of them is aromatherapy. It is an alternative medicine that uses steam from essential oils. The aims of this study is making aromatherapy formulations use the essential oils of onion. The methods are distillationing essential oils use the water, with a sample of shallots. Furthermore, aromatherapy roll on formulations were made and tested include organoleptic and physical test formulation and preference test. The results obtained on average in each distillation amounted to 0.1%, then formulated with a concentration of essential oils of 1%, 2%, 3%, 4% and 5%. Moreover according to the skin pH, the results of the physical and homogeneity test were found a pH 6 that meets the standards, and from the preference test obtained a formula containing 3% of essential oils of shallots which are most in demand by respondentsKeywords: Aromatherapy, onion (Allium cepa var. Aggregatum L), formulation